A model of assessing the economic efficiency of introducing Rosatom Production System projects to upgrade the NPP equipment - Ukhalina, I. A.; Golovko, M. V.; Agapova, S. P.; Antsibor, A. V.; Efimenko, N. A.; Rogacheva, Z. S. (Глобальная ядерная безопасность, 2023)
This article substantiates the relevance of the development and implementation of Rosatom Production System projects focused on the modernisation of equipment and technological systems of nuclear power plants. The purpose of these projects is to increase energy saving. The peculiarities of economic efficiency assessment methods based on stage-by-stage analysis of indicators by statistical and dynamic methods are considered. It is determined that the estimation procedure of economic feasibility of investing into Rosatom Production System projects on increasing energy saving has specificity depending on the content of measures. In this regard, the authors consider the results, economic and operational effects of six types of typical measures.